Mechanistic models of the ion-solvation shell system; Bulletin of the Lebedev Physics Institute; Vol. 44, iss. 9 - Shamanin I. V. Igor Vladimirovich; Kazaryan M. A. Mishik Ayrazatovich; Timchenko S. N. Sergey Nikolaevich; Ushakov I. A. Ivan Alekseevich (2017, 2017)
Title screen